PERBEDAAN TINGKAT PENGUNGKAPAN ANTARA PERUSAHAAN ASING DAN DOMESTIK DENGAN ADANYA KONVERGENSI IFRS - Yohana Heru Krisna Silviana; PratiwiÂ Budiharta (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2015)
The main purpose of this study is to determine the level of disclosure diferences between foreign and domestic companies. Tis study was focused on companies that involved in Foreign Direct Investment (FDI) and Domestic Investment (DI). In this study, FDIis the criteriaforforeign companies, whileDIis the criteriafordomestic companies. 450 companies were observed and 86 companies obtained as samples with a purposive sampling method. Tis study usinf Chi-Square and Mann-Whitney-Wilcoxon test analysis. IFRS disclosure checklist f rom PwC was used to analyze the level of disclosure. Te level of disclosure measures with Total Discosure Ratio. Also, the fnding of this study reveals that there are deferences in the level of disclosure between foreign and domestic company.Keywords: Level of disclosure, foreign company, domestic company and IFRS.